Effects Dietary of Arginine and N-carbamylglutamate on Heamatological and Performance Traits of Female Rabbits - Adil Jabbar Atiyah (Diyala Journal for Veterinary Sciences, 2025)
The influences of NCG and Arginine on female rabbits were measured in this study and focused on feed intake, body weight, and daily weight increasing, then the various parameters, especially in the blood tests, have been checked for more clear information on their usage on rabbits production and health. The experiment lasted 9 weeks with 21 female rabbits aged 5-6 months and an average weight 830 ±22 g divided into three groups, each group three rabbits. The control group was fed a basal diet, and second group was fed Arginine (300mg/ orally daily), while the third group was fed NCG (300 mg/ orally daily). The results of adding Arginine and NCG showed no significant (P<0.05) differences in body weight gain (BWG) and feed conversion ratio (FCR) among various dietary treatments recorded from one week to seven. In week eight there was a significant increase in weight gain between Arg and NCG group compared with control, the hematological test showed no significant in WBC, Hb, PCV, Thrm, RBC, group ARG and NCG compared with control. The ALT, AST and ALP enzyme appeared no significantly change(P<0.05) as well as urea concentration and total protein . It can be concluded that arginine and N-carbamylglutamate have a positive effect on rabbits’ performance by improving the productive characteristics of rabbits and not having any harmful effects on the liver and kidneys.